Research Brief #1: The Nutrition Collaborative Research Support Program (Nutrition CRSP): Planned Activities in Nepal. - Webb, Patrick, 1959-; Kennedy, Eileen T., 1947-; Ghosh, Shibani A., 1973-; Marino-Costello, Elizabeth.; Sapkokta, Diplav. (Tufts University. Tisch Library., 2016)
This briefing paper describes the background of USAID CRSPs (now called Innovation Labs); specifically the aims and research targets of the Nutrition CRSP (now Innovation Lab) Keywords: CRSP, Research Brief, Planned Activities.